Academic Burnout in Vocational High School Students - Abd. Basith; Md. Shahinoor Rahman; Usina Robert Moseki (STKIP Singkawang, 2023)
The objectives of this study were: 1) to describe the level of student academic burnout, 2) to analyze differences in student academic burnout based on gender, major, class, and ethnicity. This study uses a quantitative method with a survey design. The population is 570 students of SMK Negeri 3 Singkawang. Then, 287 students (81 male and 206 female) were taken as a sample using simple random sampling technique. The instrument used in data collection is the academic burnout scale. Data were analyzed using descriptive test and univariate test. The results showed that the students academic burnout was at a moderate level which was dominated by the cynism aspect. Then there were significant differences related to academic burnout in students based on gender and major.